Dietary Flavonoids from Modified Apple Reduce Inflammation Markers and Modulate Gut Microbiota in Mice. Issue 2 (18th December 2013) - Espley, Richard V.; Butts, Christine A.; Laing, William A.; Martell, Sheridan; Smith, Hannah; McGhie, Tony K.; Zhang, Jingli; Paturi, Gunaranjan; Hedderley, Duncan; Bovy, Arnaud; Schouten, Henk J.; Putterill, Joanna; et al.
Abstract: Apples are rich in polyphenols, which provide antioxidant properties, mediation of cellular processes such as inflammation, and modulation of gut microbiota. In this study we compared genetically engineered apples with increased flavonoids [myeloblastis transcription factor 10 ( MYB10 )] with nontransformed apples from the same genotype, "Royal Gala" (RG), and a control diet with no apple. Compared with the RG diet, the MYB10 diet contained elevated concentrations of the flavonoid subclasses anthocyanins, flavanol monomers (epicatechin) and oligomers (procyanidin B2), and flavonols (quercetin glycosides), but other plant secondary metabolites were largely unaltered. We used these apples to investigate the effects of dietary flavonoids on inflammation and gut microbiota in 2 mouse feeding trials. In trial 1, male mice were fed a control diet or diets supplemented with 20% MYB10 apple flesh and peel (MYB-FP) or RG apple flesh and peel (RG-FP) for 7 d. In trial 2, male mice were fed MYB-FP or RG-FP diets or diets supplemented with 20% MYB10 apple flesh or RG apple flesh for 7 or 21 d. In trial 1, the transcription levels of inflammation-linked genes in mice showed decreases of >2-fold for interleukin-2 receptor ( Il2rb ), chemokine receptor 2 ( Ccr2 ), chemokine ligand 10 ( Cxcl10), and chemokine receptor 10 ( Ccr10 ) at 7 d for the MYB-FP diet compared with the RG-FP diet ( P < 0.05). In trial 2, the inflammation marker prostaglandin E2 (PGE2 ) in the plasma of mice fed the MYB-FP diet at 21 d was reduced by 10-fold ( P < 0.01) compared with the RG-FP diet. In colonic microbiota, the number of total bacteria for mice fed the MYB-FP diet was 6% higher than for mice fed the control diet at 21 d ( P = 0.01). In summary, high-flavonoid apple was associated with decreases in some inflammation markers and changes in gut microbiota when fed to healthy mice.